1998
DOI: 10.2323/jgam.44.147
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of a novel lipase from Burkholderia sp. YY62 which hydrolyzes t-butyl esters effectively.

Abstract: Lipases (EC 3.1.1.3, glycerol ester hydrolase) catalyze the hydrolysis of triacylglycerols to glycerol and free fatty acids. Recently, a variety of new applications of lipase have emerged, especially in enantioselective hydrolysis of esters (Nakano et al., 1994;Tsai and Wei, 1994;Waagen et al., 1994;Wu et al., 1990), ester synthesis in organic solvents (Anderson and Callahan, 1960;Armstrong et al., 1988;Bornscheuer, 1995;Klibanov, 1989;Loffet et al., 1989;Makita et al., 1987;Turner and Winterman, 1995) and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This feature made the C. parapsilosis enzyme the catalyst of choice for the direct bioconversion of oils in aqueous medium (Vaysse et al, 1997). Yeo et al (1998) reported a novel lipase produced by Burkholderia sp., which could preferentially hydrolyze a bulky ester, t-butyl octanoate (TBO). This lipase was confirmed to be 100-fold superior to commercial lipases in terms of its TBO-hydrolyzing activity.…”
Section: Lipases In Bioconversion In Aqueous Mediamentioning
confidence: 99%
“…This feature made the C. parapsilosis enzyme the catalyst of choice for the direct bioconversion of oils in aqueous medium (Vaysse et al, 1997). Yeo et al (1998) reported a novel lipase produced by Burkholderia sp., which could preferentially hydrolyze a bulky ester, t-butyl octanoate (TBO). This lipase was confirmed to be 100-fold superior to commercial lipases in terms of its TBO-hydrolyzing activity.…”
Section: Lipases In Bioconversion In Aqueous Mediamentioning
confidence: 99%
“…4). Although tert-butyl esterhydrolyzing esterases are uncommon (54,55), these enzymes are expected to hydrolyze TBF, TBAc, and TBP to TBA and the corresponding acid. We have not quantified formate production from TBF hydrolysis, but we have confirmed that M. vaccae JOB5 does not grow on formate, MTBE, TBA, TBF, or formaldehyde as sole sources of carbon and energy.…”
Section: Vol 69 2003 Mtbe Degradation By Mycobacterium Vaccae Job5 801mentioning
confidence: 99%
“… Cheese Industry for improvement of flavor [ 709 ] Penicillium roquefortii Cheese Industry for cheese ripening [ 710 ] Staphylococcus warneri, S. xylosus Production of flavour esters [ 711 ] Pseudomonas cepacia Biodiesel fuel production [ 712 ] Pseudomonas sp. Formation of (−)-15-deoxyspergualin 23) in drug industry as antitumor antibiotic and immunosuppressive agent [ 713 ] …”
Section: Sources For Microbial Lipasesmentioning
confidence: 99%